“interacciones medicamentosas potenciales en recetas medicas en el servicio de neurocirugía 13B del Hospital Nacional Edgardo Rebagliati Martins durante el periodo febrero - julio del 2007 - Sánchez García, Mavila Julissa (2008)
The objective of the present investigation work was of identifying, to quantify and Tipificar the interactions potential present medicamentosas in the medical precripciones of the Neurosurgery of the National Hospital Edgardo Rebagliatti Martins. The present investigation work is a study decriptivo, traverse and retrospective, for the one which, 2982 were analyzed you prescribe patients medicas hospitalized in the service of Neurosurgery of H.N.E.R.M, in the period of February. Julio the 2007, of these, 2912 fulfilled the inclusion approaches, which were subjected to evaluation to determine the interactions medicamentosas, by means of the bibliographical method. analytic, being at the end, 1495 recipes with interactions potential medicamentosas. It was found that 51,34% of the recipes presented interactions potential medicamentosas, among the most frequent: Phenytoin – Ranitidine (18,98%), Paracetamol – Phenytoin (9,05%), Diazepam – Ranitidine (7,47%), Dexamethasone – Phenytoin (6,75%), Ibuprofen – Ranitidine (6,31%), Alprazolam – Phenytoin (4,77%). The interactions of clinical significancia 1, 2 and 3 represented 34,19% of the total of identified interactions. The medications that were involved most often were: Phenytoin, Paracetamol, Dexamethasone, Amikacin and Warfarin. The Pharmacist's active participation is suggested to detect and to prevent the setting-up of effects adverse devinientes of the interactions mediating medicamentosas an intense farmacovigilancia.